Catalog of the genus Glenea Newman, 1842 (Coleoptera: Cerambycidae: Lamiinae: Saperdini) with key to the sub-genera in the Philippines - Medina, Milton Norman D.; Cabras, Analyn A.; Torrejos, Chrestine; Pepito, Mark John; Barsevskis, Arvids; Mantilla, Leslae Kay Cataytay; Vitali, Francesco (Vol. 150, No. 6B (December 2021) pages 1663-1673.)
A comprehensive and updated catalog of the genus Glenea Newman, 1842 is presented with the key to the sub-genera for Philippine species. The genus counts 87 species (77 species and 10 subspecies), ranged in seven subgenera. Glenea caraga invittaticollis Breuning, 1966 rest. status= Glenea caraga subvittaticolis Breuning, 1968 n. syn. (un. repl. nom). -Title page.